Strain-dependent modulation of conductivity in single-layer transition-metal dichalcogenides - Ghorbani-Asl, Mahdi; Borini, S.; Kuc, Agnieszka B; Heine, Thomas (Physical Review B - Condensed Matter and Materials Physics, 2013)
Quantum conductance calculations on the mechanically deformed monolayers of MoS2 and WS2 were performed using the nonequlibrium Green's functions method combined with the Landauer-Büttiker approach for ballistic transport together with the density-functional-based tight binding method. Tensile strain causes significant changes in the electronic structure of transition-metal dichalcogenide single layers and eventually the semiconductor-metal transition occurs for elongations as large as 11% for the 2D-isotropic deformations in the hexagonal structure. This transition enhances the electron transport in otherwise semiconducting materials. © 2013 American Physical Society.
CRIS-Team Scopus Importer:2023-03-20